Prevalência e fatores associados ao abuso e provável dependência de álcool entre idosos da zona urbana do município de Uberaba-MG - GUIMARÃES, Mariana Silva Freitas (2016)
Alcoholism is a chronic disease characterized by addiction to alcohol. Among the elderly, the consumption is increasing substantially each day, contributing to the development of morbidities, number of mortalities and hospitalizations. Physiological changes due to old age increase the effects of alcohol on the body, so the elderly are more prone to illness. Thus, it is essential to know the factors associated with its occurrence in the elderly, in order to contribute to the elucidation of this phenomenon and contribute to its prevention. This study aimed to verify the prevalence of alcohol abuse and probable dependence in the elderly; describing the sociodemographic and economic characteristics as well as indicatives of the presence of depressive symptoms and morbidities of the elderly living in the urban area of the city of Uberaba-MG; and to verify the association between abuse and probable alcohol dependence with the variables: gender, age, income, schooling, indicatives of the presence of depressive symptoms and number of morbidities. This is a household, cross-sectional and analytical survey conducted with 614 elderly people living in the urban area of the city of Uberaba-MG. We used: form for characterization of socio-demographic and economic data; Minor Mental State Examination; Older Americans Resources and Services Questionnaire; Geriatric Depression Scale; And Michigan Alcoholism Screening Test - Geriatric Version. Chi-square tests, prevalence ratio, prevalence odds ratio and multiple binomial logistic regression model (p <0.05) were performed using the Statiscal Package for Social Sciences (SPSS), version 21.0. The project was approved by the Ethics Committee on Human Research of UFTM, Nº 573.833. The prevalence of abuse and probable alcohol dependence in the elderly was 26.5%. The sociodemographic and economic characteristics of the two groups with and without abuse and probable dependence on alcohol were similar, predominantly in elderly with 60 |- 70 years old, who lived with husband, wife or partner and with schooling of 1 |- 5 years of study. Exceptions are made for the genders in which the elderly men with alcohol abuse predominated the male and for the non-abusive the female; And individual monthly income, in which the majority of elderly people with alcohol abuse received 1 -| 3 minimum wages, and those without alcohol abuse up to a minimum wage. The elderly with alcohol abuse and probable dependence and those who did not have abuse both presented a higher percentage for five or more morbidities and absence of an indication of the presence of depressive symptoms. Abuse and probable alcohol dependence were associated with males and the presence of an indication of depressive symptoms. These results contributed to the knowledge about the use, abuse and probable dependence of alcohol in the elderly, as well as the associated factors. In addition to providing subsidies for the development of health action strategies for the purpose of health promotion, disease prevention and rehabilitation of the elderly who abuse alcohol.